Botanical monoterpenes synergise the toxicity of azamethiphos in the vector of Chagas disease, Triatoma infestans (Hemiptera: Reduviidae) - Reynoso, Mercedes María Noel (2020)
objective To investigate what toxicological interactions occur when binary combinations of azamethiphos and botanical monoterpenes (eugenol, menthol or menthyl acetate) are applied to Triatoma infestans. methods The toxicity of binary mixtures of azamethiphos and sublethal doses of a monoterpene (eugenol, menthol or menthyl acetate) was evaluated in nymphs of the first stage of T. infestans. Experiments using exposure to filter papers and topical application were carried out. Values of Lethal Concentration 50% (LC50) were calculated in the first case, and values of Lethal Dose 50% (LD50) in the second. results The LC50 of azamethiphos applied on filter paper was 50.3 µg/cm2 . However, when it was simultaneously applied with a sublethal concentration of monoterpene, its toxicity increased (LC50 with eugenol = 11.20 µg/cm2 , LC50 with menthyl acetate = 5.30 µg/cm2 , LC50 with menthol = 7.26 µg/cm2 ). When applied topically, the LD50 of azamethiphos was 7.85 µg/insect, but its toxicity drastically increased when it was applied together with sublethal doses of menthol (LD50 = 0.00016 µg/insect) or menthyl acetate (LD50 = 0.00051 µg/insect). The simultaneous application with eugenol did not significantly change azamethiphos toxicity (LD50 = 12.79 µg/ insect). conclusions The toxicity of azamethiphos in T. infestans was synergised when it was applied together with eugenol, menthol or menthyl acetate on a filter paper. However, only menthol and menthyl acetate synergysed azamethiphos when mixtures were topically applied. The drastic effects of menthol and menthyl acetate in topical application experiments should be further studied as they could be the basis for developing more efficient triatomicidal products with a lower content of conventional insecticides than those currently used for controlling T. infestans.